Analisis Pendapatan Pedagang Cabai Rawit di Pasar Tradisional Ungaran Kutowingun Kabupaten Kebumen - Slamet Pamuji; Rahmat Joko Nugroho (Jurnal Kridatama Sains dan Teknologi, 2026)
The income of traditional market traders is influenced by various business-related factors that play an important role in determining the sustainability and growth of their businesses. This study aimed to analyze the effects of business duration, business capital, and working hours on the income of cayenne pepper traders at Ungaran Traditional Market, Kutowinangun District, Kebumen Regency. The research employed a quantitative approach using a survey method. The population consisted of all cayenne pepper traders at Ungaran Traditional Market, totaling 20 traders, all of whom were selected as research respondents using a saturated sampling technique. Primary data were collected through questionnaires and analyzed using multiple linear regression in SPSS version 25. The partial test results indicated that business duration had a significant effect on income (p = 0.006), but the effect was negative. Business capital had a positive and significant effect on income with a significance value of 0.000. Meanwhile, working hours did not have a significant effect on income, as indicated by a significance value of 0.833. The simultaneous test results showed that business duration, business capital, and working hours jointly had a significant effect on traders' income with a significance value of 0.000. The coefficient of determination (R²) value of 0.760 indicated that 76.0% of the variation in traders' income was explained by business duration, business capital, and working hours, while the remaining 24.0% was attributable to other factors outside the research model. Therefore, business capital was identified as the most dominant factor affecting the income of cayenne pepper traders at Ungaran Traditional Market, Kutowinangun District, Kebumen Regency